The Ottomans 1700-1923 : an empire besieged - Aksan, Virginia H. (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Originally conceived as a military history, this second edition completes the story of the Middle Eastern populations that underwent significant transformation in the nineteenth century, finally imploding in communal violence, paramilitary activity, and genocide after the Berlin Treaty of 1878. Written by a foremost scholar of the Ottoman Empire and featuring illustrations that have not been seen in print before, this second edition will be essential reading for both students and scholars of the Ottoman Empire, Ottoman society, military and political history, and Ottoman-European relations"--
Imperial crisis in the Eurasian context -- The Ottoman system circa 1700 -- Selim III and the Ottoman revolution -- Mahmud II : an Ottoman 'reign of terror' -- The great transformation -- Imperial collapse : an empire besieged -- Ottomanism and its rivals -- 1878 Berlin Treaty and consequences -- Leadup to WWI and epilogue.
First edition published as Ottoman wars, 1700-1870 : an empire besieged by Pearson Education Limited 2007.
Keywords: Turkey -- History -- 1683-1829.; Turkey -- History -- 19th century; Turkey -- History -- 20th century; HISTORY / General